2010
DOI: 10.1111/j.1600-0838.2010.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose inhaled salbutamol has no acute effects on aerobic capacity or oxygen uptake kinetics in healthy trained men

Abstract: The prevalence of asthma is higher among elite athletes than in the general population. This has resulted in the frequent use of anti-asthmatic medication such as beta2-agonists among asthmatic athletes. Beta2-agonists are on the prohibited list of WADA. The use of the beta2-agonist salbutamol is only permitted in therapeutic inhaled doses. Most studies have reported the lack of ergogenic effects of therapeutic doses of inhaled beta2-agonists measured in maximal oxygen uptake. No previous studies have examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
3
20
1
Order By: Relevance
“…Nevertheless, despite seven out of nine subjects reported minor side effects (tachycardia and tremor) in the present study, we observed no association between reported side effects and performance during the time trial. Our observations are also consistent with previous studies showing no performance-enhancing effects of inhalation of neither salbutamol nor terbutaline in different test protocols, varying from time trials (Sporer et al 2008;Norris et al 1996) to incremental (Elers et al 2012b) and submaximal bike ergometer tests to exhaustion (Pluim et al 2011;Goubault et al 2001;Sandsund et al 1998). Furthermore, Carlsen et al (1997) even observed reduced endurance performance after inhalation of 800 µg salbutamol.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, despite seven out of nine subjects reported minor side effects (tachycardia and tremor) in the present study, we observed no association between reported side effects and performance during the time trial. Our observations are also consistent with previous studies showing no performance-enhancing effects of inhalation of neither salbutamol nor terbutaline in different test protocols, varying from time trials (Sporer et al 2008;Norris et al 1996) to incremental (Elers et al 2012b) and submaximal bike ergometer tests to exhaustion (Pluim et al 2011;Goubault et al 2001;Sandsund et al 1998). Furthermore, Carlsen et al (1997) even observed reduced endurance performance after inhalation of 800 µg salbutamol.…”
supporting
confidence: 94%
“…While several studies have investigated effects of clinical therapeutic inhalation of beta 2 -agonists (2-4 puffs) on submaximal, supramaximal, and time-trial performance (Sporer et al 2008;van Baak et al 2004;McKenzie et al 1983;Carlsen et al 1997;Signorile et al 1992), effects of supratherapeutic high-dose inhalation of beta 2 -agonists are inadequately explored. To our knowledge, only one study by Elers et al (2012b), has investigated the effects of high-dose inhalation of salbutamol (40 × 200 µg) on incremental exercise performance, whereas no studies exist investigating the effects of high-dose inhaled beta 2 -agonist on muscle strength and supramaximal exercise performance.…”
mentioning
confidence: 95%
“…Furthermore, in a study by Elers et al ., high dosages of inhaled salbutamol were used to evaluate anabolic effects in well trained athletes (VO 2 max 66 mg∙ml∙min -1 ). No beneficial or harmful effects were seen on cardiopulmonary function [8]. …”
Section: Methodsmentioning
confidence: 99%
“…The recommended dosage of nebulized salbutamol is 5 mg, which would require a therapeutic use exemption for participating athletes from the world anti-doping agency (WADA) (http://www.wada-ama.org). Although such a dosage is safe in highly trained athletes [8], we routinely recommend using 1 mg of salbutamol, which we believe leads to substantial reductions in EIB in this population. The use of nebulized isotonic saline treat EIB has not been studied before, raising questions about safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Dickinson et al [11] reported no improvement in 5 km running time trial performance following inhalation of 1600 µg salbutamol. Elers et al [12] suggested inhaling an acute dose of up to 4000 µg salbutamol resulted in no improvement in cycling time to exhaustion or oxygen kinetics. Accordingly, from a performance perspective the current WADA guidelines permitting athletes to inhale up to 1600 µg in a single day appear appropriate as there is no resultant improvement in performance in non-asthmatic athletes.…”
Section: Discussionmentioning
confidence: 99%